Kreativitas Mengajar Guru PAI Guna Meningkatkan Profesionalisme Guru PAI - Mhd. Fajar Siddik; Benny Fernanda; Indah Permata Sari (Jurnal Bintang Pendidikan Indonesia, 2024)
The importance of the role of PAI teachers in shaping students' character and morals. PAI teachers as teachers of Islam in schools have a duty to provide good religious education and learning to students, so that students can understand the teachings of Islam correctly and practice them in everyday life. However, the challenge faced by PAI teachers is how to provide interesting and fun religious learning for students. In addition, with the development of technology and information, PAI teachers must be able to develop creative and innovative teaching methods to attract students' interest in studying religion. Therefore, the creativity of teaching PAI teachers is very important in increasing the professionalism of PAI teachers. By having teaching creativity, PAI teachers can provide fun, interesting and meaningful learning for students, so that students can more easily understand the teachings of Islam. In addition, teaching creativity can also improve the ability of PAI teachers to manage classes, motivate students, and improve the quality of learning provided by PAI teachers. Thus, the creativity of teaching PAI teachers has a very important role in increasing the professionalism of PAI teachers and forming good and quality student character.